Múltiples estados estacionarios en la deshidratación de etanol por destilación extractiva con glicerol (2023)
Distillation is one of the most used processes in engineering, which is why it is one of the most studied processes; Through this project, a study is carried out regarding the energy requirement and process specifications for the extractive distillation required to obtain anhydrous ethanol. The study is based on two test scenarios associated with extractive distillation which are: the classic extractive distillation process and the process focused on dividing wall columns. The study will start from the use of the chemical process simulator “Aspen Plus” with an input stream of ethanol with a percentage of water in relation to 88% and 12% respectively associated with a stream of 100 kmol/h, the solvent used for the functionality. of the extractive distillation process is glycerol which will enter the system based on a calculation taken from a specification that meets the requirements to close the recycle stream, meeting this key requirement for the process to be efficient.